Diagnosing dopamine-responsive dystonias. Issue 5 (4th June 2015) - Malek, N; Fletcher, N; Newman, E
Abstract : The clinical spectrum of dopamine-responsive dystonias (DRDs) has expanded over the last decade to comprise several distinct disorders. At the milder end of the clinical spectrum is the autosomal-dominant guanosine triphosphate cyclohydrolase deficiency syndrome (GTPCH-DRD), and at the more severe end is the much less common autosomal recessive tyrosine hydroxylase deficiency syndrome (TH-DRD), with intermediate forms in between. Understanding the pathophysiology of DRDs can help in their optimal diagnosis and management. These are conditions with the potential to be either underdiagnosed when not considered or overdiagnosed if there is an equivocal L-dopa (levo-3, 4-dihydroxyphenylalanine) response. In this article, we discuss the clinical phenotypes of these disorders, and we outline how investigations can help in confirming the diagnosis.